Midlife Leukocyte Telomere Length as an Indicator for Handgrip Strength in Late Life. (12th October 2020) - Chang, Xuling; Chua, Kevin Yiqiang; Wang, Ling; Liu, Jianjun; Yuan, Jian-Min; Khor, Chiea-Chuen; Heng, Chew-Kiat; Koh, Woon-Puay; Dorajoo, Rajkumar
Abstract: Background: Telomere attrition has been proposed as a hallmark of aging. We previously reported on the association between blood leukocyte telomere length (LTL) at midlife and risk of chronic diseases and mortality. Methods: In this study, we investigated the effect of midlife LTL and genetic proxies on 5 markers of aging outcomes, namely handgrip strength, timed up-and-go (TUG), Singapore-modified Mini-Mental State Examination (SM-MMSE) scores, anxiety, and depression indices, measured after a median 20-year follow-up in the Singapore Chinese Health Study ( N = 9581). Results: We observed a significant association between midlife LTL and handgrip strength later in life ( p = .004, p adjust = .020), as well as a nominal significant association between midlife LTL and TUG later in life ( p = .036, p adjust = .180). The weighted Genetic Risk Score (wGRS) comprising 15 previously reported LTL reducing loci in East Asians was not significantly associated with handgrip strength. However, results from Structural Equation Modeling showed that the effect of this wGRS on handgrip strength was mediated through LTL (proportion of wGRS effect on handgrip strength mediated through LTL = 33.3%, p = .010). Conclusions: Longer midlife LTL was associated with increased handgrip strength later in life.